Analisis Kesulitan Guru Kelas Bawah dalam Menerapkan Pembelajaran Tematik Kurikulum 2013 di Madrasah Ibtidaiyah - Ahmad Badawi, Jami; Enggar Kencana Dewi, Sri; Ratna Dewi, Tri (Universitas Nurul Huda, 2022)
The importance of knowing the concept of thematic learning is one of the parameters to implement. Knowing the concept, characteristics, and learning stages (planning, implementation, and evaluation), so the teacher implementing thematic learning will undergo well that is according to the meaning of thematic learning. The problem that will be explained was analyzing the under teachers' difficulty implementing thematic learning. The aim of this research was to know about planning, implementation, and evaluation in thematic learning. The type of this research used was descriptive qualitative research. The result of this research was under teachers implementing thematic learning had not been appropriate curriculum standard of thematic learning. This was able to be presented that the planning process teacher had some difficulties in the fabrication of learning devices, methods, and media selection. Meanwhile, the teacher's implementation process also encountered some difficulties in integrating one learning to another learning, learning methods that were appropriate to students' characteristics and themes. In the evaluation process, the teacher experienced a difficulty because KTSP curriculum, on the other hand, the process of the class report had to be based on the 2013 curriculum.